ln(2x^2 + 9x – 5) = 1 + ln(x^2 + 2x – 15). Express x in terms of e

ln(2x2+ 9x – 5) = 1 + ln(x2 + 2x – 15)ln(2x2+ 9x – 5) – ln(x2 + 2x – 15)= 1 ln((2x2+ 9x – 5)/(x2 + 2x – 15)) = 1(2x2+ 9x – 5)/(x2 + 2x – 15) = e(2x – 1)(x + 5)/(x + 5)(x – 3) = e (2x – 1)/(x – 3) = e2x – 1 = e(x – 3)2x – 1 = ex – 3e2x – ex = 1 – 3ex(2 – e) = 1 – 3ex = (1 – 3e)/(2 – e)

Answered by Sylvain F. Maths tutor

3996 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A curve C has equation y = (2 - x)(1 + x) + 3 . A line passes through the point (2, 3) and the point on C with x-coordinate 2 + h . Find the gradient of the line, giving your answer in its simplest form.


How to find the angle between two 3-dimensional vectors:


The quadratic equation (k+1)x^2 + (5k-3)x + 3k = 0 has equal roots, find the possible values of the real number k.


Given df/dx=2x+3 and the graph goes through (1,1), what is the function f?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences